Factors Influencing Consumer’s Intention to Buy Furniture Online in Greater Jakarta, Indonesia - Vania Valencia; Santoso Santoso; Pradita Eka Pebrianti; Muhammad Aries Satria Raharjo (Universitas Pamulang, 2020)
The purpose of this research was to examine the factors that affect the consumer’s intention to purchase furniture via online store in Greater Jakarta. Some of the factors that considered by this research as a baseline on this journal were the consumer perceptions, perceived risk and perceived benefits. In addition, this research adding another relationship between consumer’s attitude and intention to make a purchase online. An Internet-administered survey method use to Greater Jakarta citizen. Results of this research have shown that online shopping is begin to be considered successfully provide a substantial benefit to the consumer, even though the risk factor proportion still exist. The findings also show that the increased attitudes of Greater Jakarta consumers towards online furniture shopping have been significantly affected by consumer perception and benefit.